Going to green. Volume 2, Elements of sustainability [videorecording (DVD)] - Baroff, Beverly; D'Agnese, Joseph; Kiernan, Denise (Distributed by PBS Video, 2009)
The first program explores scientific innovations, community action and political reform behind advances in green building practices. Additional programs examine the future of alternative sources of fuel, the ramifications of our air quality and the basics of water quality monitoring, water pollution control, alternative watershed plans and the impact of the Clean Water Act.